The Barriers on E-Commerce Sustainability among Small and Medium Enterprises in Malaysia - Ng, Chiu Yin; Mohd Nor, Norasmiha; Hilyati Sabtu (Research in Management of Technology and Business, 2025)
In recent years, e-commerce has rapidly developed globally and has become an integral part of modern business. In Malaysia, many enterprises leverage e-commerce to expand their market share and market space. However, small and medium-sized enterprises (SMEs) face a digital divide that affects the sustainability of their e-commerce efforts. The purpose of this study is to investigate the obstacles affecting the sustainability of e-commerce among Malaysian SMEs based on a survey of entrepreneurs operating on e-commerce platforms. The study results confirm the importance of the TOE framework for Malaysian SMEs. Using quantitative methods, this study will focus on surveying SME entrepreneurs in the e-commerce field, asking them to fill out a questionnaire. The data will be analyzed using the Statistical Package for the Social Sciences (SPSS). These results may serve as a reference for identifying and addressing obstacles faced by Malaysian SMEs.